2023
DOI: 10.1007/s10529-023-03356-0
|View full text |Cite
|
Sign up to set email alerts
|

swnk plays an important role in the biosynthesis of swainsonine in Metarhizium anisopliae

Abstract: Swainsonine (SW) is the principal toxic ingredient of locoweeds, and is produced by fungi including Metarhizium anisopliae, Slafractonia leguminicola, and Alternaria oxytropis. A key enzyme in the SW synthesis pathway is a hybrid SWNK/NRPS. The downstream biosynthetic pathways of SW have been clearly analyzed by a knockout and complement of swnK in Metarhizium robertsii, but the upstream steps and the associated regulatory proteins have not been thoroughly investigated. To verify the role of swnK in the SW bio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…This temporal gene expression pattern in S. leguminicola differs from the pattern of M. anisopliae [53,54]. In those studies, the expression levels of swnT and swnK decreased after 3d and 5d.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…This temporal gene expression pattern in S. leguminicola differs from the pattern of M. anisopliae [53,54]. In those studies, the expression levels of swnT and swnK decreased after 3d and 5d.…”
Section: Discussionmentioning
confidence: 79%
“…In contrast, Huang et al [53] measured the swainsonine concentration in the fermentation broth of M. anisopliae at different timepoints and showed that the content of SW increased at 5d to a maximum of app. 0.3 mg and then decreased.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The pSilent-1 vector has been effectively used to investigate the role of genes in a variety of filamentous fungi. In Metarhizium anisopliae , pSilent-1 plasmid was used interfered with the swnk gene of the WT strain [ 42 ]. Using the pSilent-1 vector, the chr-1 gene was suppressed in Neurospora crassa , resulting in transformants that displayed resistance to chromate and reduced accumulation of chromium [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…SW-producing fungi, Alternaria Section Undifilum spp., S. leguminicola , M. robertsii , and Chaetothyriaceae spp., share more than 70% sequence consistency with the swnK gene. The gene has been confirmed to be required for the biosynthesis of SW in M. robertsii [ 14 , 31 ]. Recent research has shown that the expression of the swnK gene in A. oxytropis was closely related to the synthesis of SW [ 32 ].…”
Section: Discussionmentioning
confidence: 99%